2019
DOI: 10.1177/0748233719862728
|View full text |Cite
|
Sign up to set email alerts
|

A multibiomarker approach to evaluate the effect of polyaromatic hydrocarbon exposure on oxidative and genotoxic damage in tandoor workers

Abstract: We conducted a cohort study of tandoor workers to evaluate the relationship between the biomarkers of oxidative and genotoxic damage and exposure to polyaromatic hydrocarbons. A series of oxidative and genotoxic damage biomarkers, including urinary 8-hydroxy-2′-deoxyguanosine (8-OHdG), malondialdehyde (MDA) content, and tail moment (TM) by comet assay, was studied. A total of 76 tandoor workers and 79 demographically matched healthy individuals as controls were included. Our results showed that the tandoor wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…It was also stated in the study of Miglani et al 2 that the PAHs we detected in our study may be carcinogenic as a result of long-term exposure.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It was also stated in the study of Miglani et al 2 that the PAHs we detected in our study may be carcinogenic as a result of long-term exposure.…”
Section: Discussionsupporting
confidence: 84%
“…The smoke produced by tandoor ovens represents a major source of indoor air pollution in rural areas of the Middle East and South Asia. 1,2 A tandoor is a simple tool that has been used since prehistoric times to cook bread and heat houses (Figure 1). Women and young children constitute the majority of those exposed to tandoor smoke and/or in danger of falling into the tandoor and, therefore, face the most tandoor-related health risks.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that smokers' plasma MDA levels were larger than non-smokers. 39 Another significant study 34 was conducted on coke plant workers in China, in which workers in a coke plant were classified into a group exposed to relatively less particulate matter and a second group highly exposed to particulate matter exposed. As an internal dosage, urine concentrations of PAHs metabolites and minerals were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of 8-OHdG may operate as a biomarker for oxidative stress on DNA, although it is not a particular diagnostic for PAH exposure. 39 The rate of DNA repair processes, which involves the removal of damaged bases or complete nucleotides, is determined by the analyzed persons' health state, age, diet, metabolic activity, and behavior. 40 Additionally, biological membranes' shape and fluidity can be altered by ROS-induced membrane lipid peroxidation, which ultimately affects how well the membranes operate.…”
Section: Discussionmentioning
confidence: 99%
“…Legitimate concerns about burning fuelwood in India will not be addressed by focusing narrowly on village women’s household cooking, which resembles the kind of narrowing of vision Scott (1998) describes as ‘seeing like a state’. Concerns about fuelwood use tend to focus intensely on women, while men and their wood-related activities constitute a peripheral interest, usually associated with workplace health issues (e.g., Das et al, 2017; Miglani et al, 2019). Furthermore, to simplify deployment of interventions, development problems are often treated as if they occur in just one setting.…”
mentioning
confidence: 99%